REFERENCE MODELS FOR THE BONDRUCK AND LIGHT-WEIGHT ASSEMBLAGE BUILDINGS IN SKOPJE’S AREA - Gjorgji Dimkov (My University, 2020)
During the past few decades, construction has been characterized by high technological development. Public buildings are built of glass and steel, that is, of materials that are the result of modern technology, typical in this day and age. Residental buildings are still built of concrete and brick products, using mostly the same techniques as in the 1970’s. The question is whether it will be possible to have a greater application of wood in modern construction of residential buildings? At present, this resource is being used more or less decoratively in architecture. The main arguments in the efforts to increase the positive image of wooden products are that wood is ecological, healthy, socially acceptable, as well as stylish, beautiful and unique. The production of new houses based on the use of wood can be successful only if the total costs are competitive against the construction of other materials. Wood has become an increasingly popular material for houses and the interiors of public buildings. All surveys indicate that people appreciate wood in their living surroundings. Investors often associate the concept of "industrial" production - with the concept of poor quality. The truth should be absolutely the opposite: the production of wooden elements and whole houses in the system of industrial construction must produce better quality as opposed to on-site construction. The research is based on the comparative analysis of the experiences in building process and exploitation of bondruck and prefabricated assemblage buildings, by the examples in Skopje’s area; with attempt to demonstrate the adventages of this type of buildings in relation with the classical buildings - both from the technical-technological and from the energy savings aspect. The primary goal of this research is to form a model for valuation the bondruck and light-weight assemblage systems, including several parameters (performances): appearance (finishes), thermo and sound insulation, fire resistance, economics, structural system and construction process (technology of building), joints and connections, flexibility and energy savings. During the valuation and comparison of the determinate systems according to already defined model, there has been opened a possibility ro research new forms and creative innovative concepts for the structural systems and the single family house architecture. By analyzing the systems with this method, the values and the adventages of the bondruck and light-weight assemblage systems are recognized, and there is possibility for a truly re-affirmation of the traditional architectural form with a development of a contemporary variant, relative to applicated materials and to level of the materialization and the finishes. The research is realizated by the general, particular methods and specific procedures and techniques: analysis, comparison, synthesis, individual terrain researches and measuring, case study, interview.
Keywords: reference model, valuation, bondruck, assemblage, structural system, construction process, appearance, thermo and sound insulation, fire resistance, economics, joints and connections, flexibility, energy savings